Contrasting growth responses of Qilian juniper (Sabina przewalskii) and Qinghai spruce (Picea crassifolia) to CO2 fertilization despite common water-use efficiency increases at the northeastern Qinghai–Tibetan plateau. (24th December 2020) - Wang, Wenzhi; McDowell, Nate G; Liu, Xiaohong; Xu, Guobao; Wu, Guoju; Zeng, Xiaomin; Wang, Genxu
Abstract: Rising atmospheric carbon dioxide (CO2 ) may enhance tree growth and mitigate drought impacts through CO2 fertilization. However, multiple studies globally have found that rising CO2 has not translated into greater tree growth despite increases in intrinsic water-use efficiency (iWUE). The underlying mechanism discriminating between these two general responses to CO2 fertilization remains unclear. We used two species with contrasting stomatal regulation, the relatively anisohydric Qilian juniper ( Sabina przewalskii ) and the relatively isohydric Qinghai spruce ( Picea crassifolia ), to investigate the long-term tree growth and iWUE responses to climate change and elevated CO2 using tree ring widths and the associated cellulose stable carbon isotope ratios (δ 13 C). We observed a contrasting growth trend of juniper and spruce with juniper growth increasing while the spruce growth declined. The iWUE of both species increased significantly and with similar amplitude throughout the trees' lifespan, though the relatively anisohydric juniper had higher iWUE than the relatively isohydric spruce throughout the period. Additionally, with rising CO2, the anisohydric juniper became less sensitive to drought, while the relatively isohydric spruce became more sensitive to drought. We hypothesized that rising CO2 benefits relatively anisohydric species more than relatively isohydric species due to greater opportunity to acquire carbon through photosynthesis despite warming and droughts. Our findings suggest the CO2 fertilization effect depends on the isohydric degree, which could be considered in future terrestrial ecosystem models.